Establishing a genomic radiation-age association for space exploration supplements lung disease differentiation - Ruprecht, Nathan A.; Singhal, Sonalika; Schaefer, Kalli; Gill, Jappreet S.; Bansal, Benu; Sens, Donald; Singhal, Sandeep K. (Frontiers in Public Health, 2023)
Purpose: One possible way to quantify each individual’s response or damage from ionizing radiation is to estimate their accelerated biological age following exposure. Since there is currently no definitive way to know if biological age estimations are accurate, we aim to establish a rad-age association using genomics as its foundation. Methods: Two datasets were combined and used to empirically find the age cutoff between young and old patients. With age as both a categorical and continuous variable, two other datasets that include radiation exposure are used to test the interaction between radiation and0 age. The gene lists are oriented in preranked lists for both pathway and diseases analysis. Finally, these genes are used to evaluate another dataset on the clinical relevance in differentiating lung disease given ethnicity and sex using both pairwise t-tests and linear models. Results: Using 12 well-known genes associated with aging, a threshold of 29 years old was found to be the difference between young and old patients. The two interaction tests yielded 234 unique genes such that pathway analysis flagged IL-1 signaling and PRPP biosynthesis as significant with high cell proliferation diseases and carcinomas being a common trend. LAPTM4B was the only gene with significant interaction between lung disease, ethnicity, and sex and fold change greater than two. Conclusion: The results corroborate an initial association between radiation and age given inflammation and metabolic pathways and multiple genes emphasizing mitochondrial function, oxidation, and histone modification. Being able to tie rad-age genes to lung disease supplements future work for risk assessment following radiation exposure.